Galaxy clusters around radio-loud active galactic nuclei at 1.3 <z< 3.2 as seen by Spitzer - Wylezalek, D.; Galametz, A.; Stern, D.; Vernet, J.; De Breuck, C.; Seymour, Nick; Brodwin, M.; Eisenhardt, P.; Gonzalez, A.; Hatch, N.; Jarvis, M.; Rettura, A.; et al. (2013)
We report the first results from the Clusters Around Radio-Loud AGN program, a Cycle 7 and 8 Spitzer Space Telescope snapshot program to investigate the environments of a large sample of obscured and unobscured luminous radio-loud active galactic nuclei (AGNs) at 1.2 < z < 3.2. These data, obtained for 387 fields, reach 3.6 and 4.5 μm depths of [3.6]AB = 22.6 and [4.5]AB = 22.9 at the 95% completeness level, which is two to three times fainter than L* in this redshift range. By using the color cut [3.6] – [4.5] > –0.1 (AB), which efficiently selects high-redshift (z > 1.3) galaxies of all types, we identify galaxy cluster member candidates in the fields of the radio-loud AGN. The local density of these Infrared Array Camera (IRAC)-selected sources is compared to the density of similarly selected sources in blank fields. We find that 92% of the radio-loud AGN reside in environments richer than average. The majority (55%) of the radio-loud AGN fields are found to be overdense at a ≥2σ level; 10% are overdense at a ≥5σ level. A clear rise in surface density of IRAC-selected sources toward the position of the radio-loud AGN strongly supports an association of the majority of the IRAC-selected sources with the radio-loud AGN. Our results provide solid statistical evidence that radio-loud AGN are likely beacons for finding high-redshift galaxy (proto-)clusters. We investigate how environment depends on AGN type (unobscured radio-loud quasars versus obscured radio galaxies), radio luminosity and redshift, finding no correlation with either AGN type or radio luminosity. We find a decrease in density with redshift, consistent with galaxy evolution for this uniform, flux-limited survey. These results are consistent with expectations from the orientation-driven AGN unification model, at least for the high radio luminosity regimes considered in this sample.